Sclerostin, vascular risk factors, and brain atrophy in excessive drinkers - Martín-González, Candelaria; Godoy-Reyes, Ana María; Abreu-González, Pedro; Fernández-Rodríguez, Camino María; Martín-Ponce, Esther; Sánchez-Pérez, María José; Alvisa-Negrín, Julio César; Rodríguez-Gaspar, Melchor; González-Reimers, Emilio (Frontiers in Human Neuroscience, 2023)
Objective Heavy alcohol consumption causes several organic complications, including vessel wall calcification. Vascular damage may be involved in the development of brain atrophy and cognitive impairment. Recently, sclerostin (whose levels may be altered in alcoholics) has emerged as a major vascular risk factor. The objective of the present study is to analyze the prevalence of vascular calcifications in alcoholics, and the relationships of these lesions with brain atrophy, as well as the role of sclerostin on these alterations. Patients and methods A total of 299 heavy drinkers and 32 controls were included. Patients underwent cranial computed tomography, and several indices related to brain atrophy were calculated. In addition, patients and controls underwent plain radiography and were evaluated for the presence or absence of vascular calcium deposits, cardiovascular risk factors, liver function, alcohol intake, serum sclerostin, and routine laboratory variables. Results A total of 145 (48.47%) patients showed vascular calcium deposits, a proportion significantly higher than that observed in controls (χ2 = 16.31; p < 0.001). Vascular calcium deposits were associated with age (t = 6.57; p < 0.001), hypertension (t = 5.49; p < 0.001), daily ethanol ingestion (Z = 2.18; p = 0.029), duration of alcohol consumption (Z = 3.03; p = 0.002), obesity (χ2 = 4.65; p = 0.031), total cholesterol (Z = 2.04; p = 0.041), triglycerides (Z = 2.05; p = 0.04), and sclerostin levels (Z = 2.64; p = 0.008). Calcium deposits were significantly related to Bifrontal index (Z = 2.20; p = 0.028) and Evans index (Z = 2.25; p = 0.025). Serum sclerostin levels were related to subcortical brain atrophy, assessed by cella media index (Z = 2.43; p = 0.015) and Huckmann index (ρ = 0.204; p = 0.024). Logistic regression analyses disclosed that sclerostin was the only variable independently related to brain atrophy assessed by altered cella media index. Sclerostin was also related to the presence of vascular calcifications, although this relationship was displaced by age if this variable was also included. Conclusion Prevalence of vascular calcification in alcoholics is very high. Vascular calcium deposits are related to brain atrophy. Serum sclerostin is strongly related to brain shrinkage and also shows a significant relationship with vascular calcifications, only displaced by advanced age.